(untitled) (Nordic Journal of African Studies, 2001)
The paper describes the social function performed by the Yorùbá royal bards in the society. The data are from the Oyo-Yorùbá communities, but mutatis mutandis they can be seen to represent all the Yorùbáland, because cultural variation between different areas is limited. The bards sing and chant in honour of the kings, and they also announce the advent of important guests by drumming or piping the names and attributes of such guests as they enter the royal palace. The social responsibilities of royal bards include entertainment, the description of the qualities of the character and physical appearance of patrons, historical documentation, and image-making for their patrons. Socio-economic changes, however, have caused considerable changes in the roles of these bards. Since the economic status and the social prestige of the traditional rulers has declined, most of the male bards have become freelance minstrels in addition to the traditional trade, and they go about entertaining the public at social gatherings and even on the street. Female bards, on the other hand, have stayed loyal to the palace. (Ed.)